Judge's arguments in decisions involving Sharia economic disputes in the regional religious courts of Jakarta, 2015–2022. - Faqih Zuhdi Rahman; Mustolih Siradj; Asadurrahman Asadurrahman (Jurnal Cita Hukum, 2024)
Judges must be capable of settling sharia economic issues without departing from accepted sharia principles. When weighing each decision, the judge takes into account the DSN-MUI Fatwa, which serves as a manual and a mechanism for the implementation of sharia economic activities in Indonesia, as well as KHES, which serves as the primary legal framework for religious courts handling sharia economic disputes. This study intends to map the judges' arguments in sharia economic issues and explain how the National Sharia Council-Indonesian Ulema Council (DSN-MUI) Fatwa and the Compilation of Sharia Economic Law (KHES) are applied in Religious Court rulings involving sharia economic disputes. A qualitative approach is applied in the study methodology, which is normative legal research. The study's findings demonstrate that the judges' arguments in sharia economic matters in the Jakarta Regional Religious Court jurisdiction reflect their own viewpoints. The judge's arguments in the five Religious Courts in the Jakarta region frequently reference the Civil Code for legal justifications. The DSN-MUI Fatwa and KHES must be applied as effectively as possible. The use of KHES is only used in specific articles, namely using Articles 36 and 38 of the Compilation of Sharia Economic Law and the DSN-MUI Fatwa, which is mostly used in matters of compensation or ta'widh or sanctions for customers who are unable to fulfill their obligations, according to an analysis of sharia economic case decisions at the Jakarta Regional Religious Court.